Polyherbal formulation PL02 alleviates pain, inflammation, and subchondral bone deterioration in an osteoarthritis rodent model - Upadhyay, Prabhat; Kalra, Diya; Nilakhe, Aishwarya Shrikant; Aggrawal, Vijay; Gupta, Sarika (Frontiers in Nutrition, 2023)
Introduction Osteoarthritis (OA) is a debilitating disease with significant personal and socioeconomic burdens worldwide. Methods To address this, we developed a multitargeted formulation called PL02, which includes standardized extracts of Rosa canina L, Hippophae rhamnoides, and collagen peptide. We tested the pharmacological efficacy of PL02 in a rodent model of OA induced by Monosodium iodoacetate (MIA). Results Our results demonstrate that oral administration of PL02 has antioxidant effects by down-regulating NOS, reduces pain-related behavior, and mitigates inflammation by inhibiting IL-1b and TNF-α production, as well as downregulating CGRP1 and COX-II. PL02 also exhibits anti-catabolic and chondroprotective activity by significantly downregulating MMP13 and upregulating BCL2. Additionally, PL02 demonstrates chondrogenic activity by significantly upregulating SOX-9 (a master regulator of chondrogenesis), Coll-I, and aggrecan, which are major components of articular cartilage. Furthermore, PL02 prevents microarchitectural deterioration of subchondral bone. Conclusion Overall, PL02 is an orally active, multi-targeted therapy that not only alleviates pain and inflammation but also effectively halts cartilage and subchondral bone deterioration. It represents a safe and promising candidate for the treatment and management of OA.